“We do not want the Commission to allow the families to disappear into thin air”: A consideration of widows’ testimonies at the Truth and Reconciliation Commission and the Farlam (Marikana) Commission of Inquiry - Kros, Cynthia (PINS-Psychology in Society, 2017)
Using Gayatri Spivak’s famous question about whether the “subaltern” can speak, this article addresses the testimonies given to the Farlam Commission of Inquiry by the widows of miners who had been killed in police shootings while engaged in an unprotected strike at Lonmin’s platinum mine at Marikana in August 2012. The widows were required to face down the dominant narrative disseminated by mine management and other business as well as state interests, which held that the police had acted in self-defence after the strikers had threatened to attack them. I argue that the widows consciously sought to undo the dominant narrative through their testimonies, assuming the role of a new kind of “political widow” as theorised by Mamphela Ramphele (1996). The article begins with a detailed consideration of the testimony of Sepati Mlangeni whose husband had been murdered by an agent of the apartheid state, delivered to the Truth and Reconciliation Commission (TRC) in the 1990s. This sets the scene for the questions that might be asked and the observations made of the Marikana widows’ testimonies presented to the Farlam Commission almost twenty years later.